Selecting an intervention to prevent ketoacidosis at diabetes diagnosis in children using a behavior change framework. Issue 3 (15th January 2022) - Koripalli, Maanasa; Giruparajah, Mohana; Laur, Celia; Shulman, Rayzel
Abstract: Objective: The rate of diabetic ketoacidosis (DKA), a preventable, life‐threatening complication of diabetes, at the time of diagnosis in children remains unacceptably high worldwide. We describe our initial approach to selecting a national DKA prevention strategy, to be implemented by the Canadian Pediatric Endocrine Group DKA Prevention Working Group, informed by a framework for behavior change interventions. Methods: Existing interventions were identified from a systematic review and our own gray literature search. We then characterized interventions using the Behavior Change Wheel, a framework to inform and drive behavior change, and matched interventions to behavioral targets, audiences, and identified barriers and facilitators. Feedback from the CPEG DKA prevention working group was incorporated into the intervention plan. Results: We identified 27 interventions. Our proposed target behaviors are: (1) prompt recognition of symptoms of diabetes in children; (2) urgent attendance to medical care with a request for an office‐based test for diabetes; and (3) rapid confirmation of diagnosis and urgent consultation with pediatric diabetes experts. We initially identified four possible intervention functions including education, training, environment restructuring, and enablement. Feedback from the working group favored education intervention functions including symptom recognition messages targeting parents, caregivers, teachers, and providers and messages about how to make a rapid diagnosis and need for urgent referral targeting providers. Conclusions: The Behavior Change Wheel has been used successfully in selecting interventions in other clinical areas. We describe how we used this framework to provide a foundation for developing an intervention to prevent DKA at diabetes diagnosis in children.